Psychlogical Well- Being pada Janda Dewasa Awal Karena Perceraian - Ardia Indah Cahyani; Retno Dwiyanti (PSIMPHONI, 2021)
The psychological well-being of widows can be seen from how they can have good self-acceptance, positive relationships with others, good independence, life goals, and also environmental mastery and good self-development. The study aimed to determine the psychological well-being of widowed early adult women because of divorce. The subjects in this study were 3 informants who are all widows and are in the young adult development phase in which the age range of the subjects was 22 years to 40 years and supported by three secondary subjects. The subjects were widowed because of the death of the spouse and divorce due to conflicts in the household. This research was qualitative with a case study. The data in this study were collected using interviews and observation. The result of this research illustrated that a widowed woman in the early adult phase because of the divorce did not have full psychological well-being yet. A good psychological well-being happened when aspects of psychological well-being could be achieved by the subject. However, the subject in this study did not fully feel good in self-acceptance when being left by her partner. Furthermore, independence was also closely related to its status, particularly when the widow did not have a permanent job. In addition, there were differences and similarities between the three subjects found in this study, the lack of psychological well-being of the three subjects was mostly due to their past experience, the relationship of the subjects with the people around them and the independence of the subject in dealing with life problems. The environmental mastery of the three subjects was also considered as low.